Achievement Emotions and Academic Performance: Longitudinal Models of Reciprocal Effects. Issue 5 (8th February 2017) - Pekrun, Reinhard; Lichtenfeld, Stephanie; Marsh, Herbert W.; Murayama, Kou; Goetz, Thomas
Abstract : A reciprocal effects model linking emotion and achievement over time is proposed. The model was tested using five annual waves of the Project for the Analysis of Learning and Achievement in Mathematics (PALMA) longitudinal study, which investigated adolescents' development in mathematics (Grades 5–9; N  =   3, 425 German students; mean starting age = 11.7 years; representative sample). Structural equation modeling showed that positive emotions (enjoyment, pride) positively predicted subsequent achievement (math end‐of‐the‐year grades and test scores), and that achievement positively predicted these emotions, controlling for students' gender, intelligence, and family socioeconomic status. Negative emotions (anger, anxiety, shame, boredom, hopelessness) negatively predicted achievement, and achievement negatively predicted these emotions. The findings were robust across waves, achievement indicators, and school tracks, highlighting the importance of emotions for students' achievement and of achievement for the development of emotions.